2002
DOI: 10.1073/pnas.022615199
|View full text |Cite
|
Sign up to set email alerts
|

Experience-dependent changes in cerebellar contributions to motor sequence learning

Abstract: Studies in experimental animals and humans have stressed the role of the cerebellum in motor skill learning. Yet, the relative importance of the cerebellar cortex and deep nuclei, as well as the nature of the dynamic functional changes occurring between these and other motor-related structures during learning, remains in dispute. Using functional magnetic resonance imaging and a motor sequence learning paradigm in humans, we found evidence of an experience-dependent shift of activation from the cerebellar cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
266
5
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(311 citation statements)
references
References 39 publications
(46 reference statements)
35
266
5
5
Order By: Relevance
“…In contrast, the role of the SMA during the learning of skillful movement sequences remains less well understood. The SMA was activated in some imaging studies when subjects performed previously learned movement sequences compared with new sequences (Doyon et al 2002;Grafton et al 1998;Jenkins et al 1994), but this activation was not consistently observed in other studies (Rauch et al 1995(Rauch et al , 1997Sakai et al 1998Sakai et al , 2002Willingham et al 2002). The reason for this discrepancy is not known, although it might be related to the differences in the behavioral paradigms.…”
Section: Introductionmentioning
confidence: 42%
See 1 more Smart Citation
“…In contrast, the role of the SMA during the learning of skillful movement sequences remains less well understood. The SMA was activated in some imaging studies when subjects performed previously learned movement sequences compared with new sequences (Doyon et al 2002;Grafton et al 1998;Jenkins et al 1994), but this activation was not consistently observed in other studies (Rauch et al 1995(Rauch et al , 1997Sakai et al 1998Sakai et al , 2002Willingham et al 2002). The reason for this discrepancy is not known, although it might be related to the differences in the behavioral paradigms.…”
Section: Introductionmentioning
confidence: 42%
“…Previous lesion and imaging studies have suggested that the SMA plays a role in the retrieval and execution of previously learned movement sequences (Doyon et al 2002;Goldberg 1985;Grafton et al 1995Grafton et al , 1998Hazeltine et al 1997;Jenkins et al 1994;van Mier et al 1998). However, lesion studies tend to focus disproportionately on the functional deficit resulting from a particular lesion rather than on functions that might be normally supported by a given cortical area but spared by the lesion due to redundancy or recovery.…”
Section: Comparison To Previous Studiesmentioning
confidence: 97%
“…Notwithstanding, increased cerebellar activation was reported during movement imagination [Decety et al, 1994;Jueptner et al, 1997], preparation [Deiber et al, 1996;Krams et al, 1998], and observation with the aim to imitate [Grèzes et al, , 1999, although the highest activations are usually found during actual movement execution [Deiber et al, 1996;Jueptner et al, 1997;Krams et al, 1998]. Cerebellum plays also a significant role in the early phases of acquisition and planning of motor sequences [Doyon et al, 2002], and is known to participate in a wide variety of cognitive and emotional processes [e.g., see Marien et al, 2001;Middleton and Strick, 1998;Rapoport et al, 2000;Salman, 2002]. Moreover, a modular organization of internal models of tool manipulation has been recently reported in the cerebellum using fMRI [Imamizu et al, 2003], extending the predictions of the MOSAIC computational model [Haruno et al, 2001;Wolpert and Kawato, 1998] from to the "motor" to the "cognitive" cerebellum.…”
Section: Innervatory Patternsmentioning
confidence: 99%
“…It remains a puzzle, however, as to which conditions lead to reduced or enhanced activations as a result of perceptual learning. It should be noted that brain imaging studies of motor skill learning have also reported both types of effect (Karni et al, 1995;Doyon et al, 2002;Wu et al, 2004), and no hypothesis has yet provided a sufficient explanation for this unresolved issue.…”
Section: Changes In Visual Cortex Activation During Perceptual Learningmentioning
confidence: 99%